Authors, Online - Gervais, Daniel (The Columbia Journal of Law & the Arts, 2015)
The copyright chapter of the Internet story is familiar to all of us by now: the Internet provides access to an incredible array and variety of cultural products from around the world. It is the Great Virtual Library, available at your local caf6 and everywhere else. It makes cultural products not only easier to access but also to modify (and to disseminate the modified versions). Because the Internet allows access and easy reuse, the Internet is the Global Meme Factory–it makes possible a great cycle of: (1) access to existing works; (2) copying them; (3) modifying them and (4) disseminating them, which repeats endlessly in various directions. The Internet offers major advantages for authors (though there are downsides, and I will discuss those later), users and new intermediaries.